Flipped v's traditional teaching perspectives in a first year accounting unit: an action research study. (4th July 2019) - Williams, Belinda; Horner, Claire; Allen, Stephen
ABSTRACT: With the need to move accounting students towards deeper learning approaches and understandings, this first cycle of an action research study sought to determine the student's perspective of the flipped learning approach. With this learning approach gaining momentum in recent times, this study focuses on a first-year introductory accounting class in an undergraduate business degree. In making changes to the learning environment, we survey students and find that there are significant differences between the flexible student, that is, students that are already exposed in a limited way to this approach, and the face-to-face student. Results indicate further action research is required if the flipped learning approach is to be considered a serious teaching and learning contender for the first-year student.